2011
DOI: 10.1055/s-0031-1293203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment and Management of the Endometrium in Recurrent Early Pregnancy Loss

Abstract: Unexplained and recurrent loss of pregnancies is a heartbreaking and frustrating condition. The routine diagnostic workup for pregnancy loss includes hormonal evaluation, screening for genetic or chromosomal defects, immunologic and thrombophilic testing, and evaluation of congenital or acquired Müllerian defects. In cases of idiopathic pregnancy loss, defects in endometrial receptivity are increasingly being investigated. The role of the endometrium in pregnancy loss has historical roots but remains controver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 212 publications
(262 reference statements)
0
20
0
Order By: Relevance
“…The incidence of RSM in women of reproductive age seeking pregnancies is reported to be 1-2% [1,2,3,6,13,14]. RSM, which is distressing to the affected families [13] and the couple seeking parenthood, has been a formidable challenge for the treating physician [15]; it has also been regarded as a heartbreaking and frustrating condition [16]. Patients presenting with RSM have experienced psychological trauma as they face the uncertainty of the outcome of the next pregnancy, and a variety of psychological and psychiatric disorders including anxiety, depression, posttraumatic stress disorders, and obsessive-compulsive disorders develop in these patients after RSM [17].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of RSM in women of reproductive age seeking pregnancies is reported to be 1-2% [1,2,3,6,13,14]. RSM, which is distressing to the affected families [13] and the couple seeking parenthood, has been a formidable challenge for the treating physician [15]; it has also been regarded as a heartbreaking and frustrating condition [16]. Patients presenting with RSM have experienced psychological trauma as they face the uncertainty of the outcome of the next pregnancy, and a variety of psychological and psychiatric disorders including anxiety, depression, posttraumatic stress disorders, and obsessive-compulsive disorders develop in these patients after RSM [17].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these observations, Endo rats ovulate fewer oocytes, develop fewer zygotes and at gestational day 15 have fewer viable fetuses and more pregnancy loss than Sham rats (26). In addition, Vernon MW and Wilson EA (25), the individuals who developed this endometriosis model, reported that the induction of endometriosis significantly reduced the number of pups at term by 48%.…”
Section: Introductionmentioning
confidence: 99%
“…These events included cytoplasmic fragmentation, darkened cytoplasm and arrest before syngamy, reduced embryo cell numbers (7, 11, 12). Increased frequency of embryo arrest (7, 13), decreased implantation rates (7, 11, 14, 15) and early pregnancy loss (8, 16, 17, 18, 19, 20) are also present in women with endometriosis. Yet others have not found such anomalies (21, 22, 23, 24) and this topic remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans and farm animals, early pregnancy loss occurs most frequently during the peri-implantation period mainly due to uterine dysfunction and/or abnormal conceptus (embryo and extraembryonic membranes) development (Tuckerman et al 2004, Dixon et al 2007, Patel & Lessey 2011, Koot et al 2012. The incidence of early pregnancy loss in humans is estimated to be 30% prior to conceptus implantation and 30% before 6 weeks of pregnancy (Teklenburg et al 2010).…”
Section: Introductionmentioning
confidence: 99%